2021
DOI: 10.6018/analesps.383941
|View full text |Cite
|
Sign up to set email alerts
|

Relaciones de la motivación con la metacognición y el desempeño en el rendimiento cognitivo en estudiantes de educación primaria

Abstract: Diversas investigaciones destacan la importancia de la motiva-ción en el rendimiento cognitivo y también la importancia de la motivación en la metacognición. El objetivo de esta investigación es indagar en las va-riables motivacionales que influyen en el rendimiento de tareas cognitivas y en la metacognición. La investigación se ha realizado en un colegio público de la Comunidad de Madrid. La muestra de este estudio corresponde a 354 alumnos de educación primaria, entre los 8 y 11 años de edad. Los instru-ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…In the same way, the value assigned to the activities determined by a motivating attitude was associated with the effective use of these strategies from the approaches of Khan and Rasheed [40]. These findings were also corroborated in the research by Nieto-Márquez et al [41] and Cui et al [42] who investigated the relationship between learning strategies and motivation in a group of university students. The results indicated that the students that used cognitive and metacognitive strategies had a greater motivation and, hence, a greater performance.…”
Section: Discussionsupporting
confidence: 65%
“…In the same way, the value assigned to the activities determined by a motivating attitude was associated with the effective use of these strategies from the approaches of Khan and Rasheed [40]. These findings were also corroborated in the research by Nieto-Márquez et al [41] and Cui et al [42] who investigated the relationship between learning strategies and motivation in a group of university students. The results indicated that the students that used cognitive and metacognitive strategies had a greater motivation and, hence, a greater performance.…”
Section: Discussionsupporting
confidence: 65%
“…Together, the lack of perseverative responding and shortened reward latencies suggest that the highly motivational quality of the liquid reward was sufficient to overcome the effects of moderate PAE. Interestingly, enhancing motivational state has been shown to improve cognitive performance in rodents ( Avlar et al, 2015 ) and humans ( Nieto-Márquez et al, 2021 ) and has provided a framework for using intrinsic motivation states to improve cognitive abilities in neurodegenerative ( Braver et al, 2014 ; Manera et al, 2017 ; Ruiz-González et al, 2021 ), neurodevelopmental ( Prins et al, 2011 ; Demurie et al, 2012 ), and neuropsychiatric disorders ( Choi and Medalia, 2010 ). The current data suggest that the motivational state may be a target for enhancing therapeutic efficacy in FASD.…”
Section: Discussionmentioning
confidence: 99%
“…Como se ha expuesto, estos estudios conllevan a la motivación de los estudiantes, por lo que también se ha revisado en la literatura existente, acerca de la motivación para el desempeño en el rendimiento cognitivo en estudiantes (Nieto-Márquez et al 2021); los conceptos y diferenciación de la motivación intrínseca y extrínseca para el aprendizaje (Álvarez Martínez & Rojas Ochoa, 2021); la motivación extrínseca para el aprendizaje de matemáticas (Tarira Caice et al 2018), y también acerca de motivación para el aprendizaje en cursos virtuales (Abril Lancheros, 2018). Por último, como factor de aprendizaje orientada a la actividad formativa, que establece que el ser humano es un constructor activo de su realidad y que el conocimiento es una construcción individual, se menciona a la Teoría del constructivismo como método de aprendizaje planteado por Vico y Kant en el siglo XVIII (Ortiz Granja, 2015).…”
Section: Marco Teóricounclassified